Aryl hydrocarbon receptor regulates the expression of LmGSTd7 and is associated with chlorpyrifos susceptibility in Locusta migratoria. Issue 11 (26th September 2019) - Zhang, Xueyao; Jie, Dong; Liu, Jiao; Zhang, Jianqin; Zhang, Tingting; Zhang, Jianzhen; Ma, Enbo
Abstract: BACKGROUND: The aryl hydrocarbon receptor (AhR) belongs to the bHLH‐PAS (basic Helix–Loop–Helix – Period/ARNT/Single minded) family of transcription factors. AhR is a ligand‐activated transcription factor, which participates in the sensing and transmitting stimuli of endogenous and exogenous chemicals, and subsequently activates the transcription of genes related to various physiological and detoxification functions. RESULT: In this study, a single full‐length LmAhR sequence was cloned and characterized. RNA interference (RNAi) and insecticide bioassays showed that LmAhR plays a vital role in chlorpyrifos susceptibility. To better identify aryl hydrocarbon receptor from locusta migratoria (LmAhR)‐regulated genes involved in chlorpyrifos susceptibility, a comparative transcriptome analysis was performed using double‐stranded (ds) GFP ‐ and ds LmAhR ‐injected Locusta migratoria . Differential gene expression analysis identified 145 down‐regulated and 67 up‐regulated genes ( P ≤ 0.05 and fold change ≥2) in ds LmAhR ‐knockdown insects. We selected 27 down‐regulated genes and verified their expression levels using reverse transcription quantitative PCR. Finally, one glutathione S ‐transferase (GST) gene ( LmGSTd7 ) was selected as a candidate detoxification gene and was further validated via RNAi and chlorpyrifos bioassays. CONCLUSION: Our data suggest that AhR is associated with chlorpyrifos susceptibility via the regulation of LmGSTd7 expression in L. migratoria . © 2019 Society of Chemical Industry Abstract : AhR is associated with chlorpyrifos susceptibility via the regulation of LmGSTd7 expression in L. migratoria .